REVIEW OF GEOTHERMAL POTENTIAL IN INDONESIA AND THE IMPACT ON CLIMATE CHANGE IN THE FUTURE (UIR PRESS, 2025)
Electricity is crucial at this time, but the challenge lies in reducing and replacing the use of fossil fuels, as continuous use will exacerbate climate change and harm the world. The best solution is to replace it with new renewable energy sources, such as geothermal energy, which has significant potential in Indonesia. The most considerable geothermal potential in the world is 29.038 MW. This paper uses the literature review method. The criteria for articles used as sources are research-type articles. The purpose of this article is to review the geothermal potential in Indonesia, which can be utilised and developed to reduce the use of fossil energy, which has negative impacts in the future, so that this potential can be used optimally.